FOOTBALL: THE SUCCUMBED HISTORY TO RACIAL INTOLERANCE (Fiep Bulletin - online, 2015)
This paper is about racial intolerance in Brazilian football, based on the understanding that we are known as the country of football and that adjective was given by our unique way of playing. Our swagger, skill, ability to improvise is a consequence of the formation of the Brazilian people and the sport being the reproduction of the society we live in, our beautiful game acquired this identity, football art, and it also had the inclusion of blacks, and black descedants as the primary factor for this situation. At a time when racial discrimination was exacerbated, Gilberto Freyre and Mário Filho, postulated a racial democracy through football. However, what has been happening throughout history is the spread of racism in our society, with numerous occurrences inside the stadiums. In this year 2014, two points has getting our attention to these fateful events, the incidence of cases and the encouragement of victims to report these attacks. Among these incidents the "Aranha case" had a great impact, however, this does not mean that this case is more serious than the others, the violence of these racist acts are of the same magnitude. To elaborate this paper, it was realized a review of the literature with emphasis on authors who critically address the insertion of black in football and how the desired racial democracy, through sport, has been succumbed by racial intolerance.
Keywords: Football. Racism. Societ.